Study the improvement of thermo - mechanical properties for polyester adhesive by using different fibers (glass, kevelar, and carbon). - Abass, F.U.; lbraheem, S. E.; Abass, R.U. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The   mechanical    properties   of   fiber-reinforced-polymer   (FRP)composites are dependent on the type amount, and orientation of fiber that is selected for a particular service. There are many commercially available reinforcement forms to meet the design requirements of the user. The ability of failure in the fiber architecture allows for optimized performance of a product that saves both weight and cost ( 12).A modem technology is adopted to produce fibers (glass, kevelar,and carbon) reinforced composite by using unsaturated polyester, where different volume fraction  of these fibers are used  (0, 0.2, 0.4, 0.6, 0.8,  I)reinforcement to unsaturated polyester and the samples are cured at 25C for 24hrs.The results of thermo-mechanical properties indicates that:-AJI the mechanical  properties are improved for composite samples withpreference for kevelar fiber, and good thermal properties are appeared with preference for carbon fiber. All these re ults are explained on the surface of research.